Prilaku Masyarakat Melakukan Pinjaman Kepada Rentenir Ditinjau Dalam Persepektif Sosial Ekonomi Keluarga (Studi Kasus Di Kelurahan Tanjung Unggat Kota Tanjungpinang) - Muhammad Ilham (AGHNIYA : Jurnal Ekonomi Islam, 2020)
The study of economic opportunities is very interesting, because a person's views on the economy also affect his social status, so there is a different role when viewed from the economic side. However, there are times when the business has been maximized but the needs have not been good, it is not uncommon to make many loans to financial providers, one of which is moneylenders by reason of easy requirements given.This research is a qualitative research with the type of field research (Field Research). Besides that, this research also uses data collection techniques in the form of observation, interviews and documentation. While the sampling technique in the form of purposive sampling technique.As for the results obtained that there are 2 (two) reasons for the people of Tanjung Unggat Urban Village Tanjungpinang City to lend money to moneylenders, namely the reasons for the requirements that are easily met and the reasons for being forced in a relatively short time. Besides that, the impact found after making loans in the socioeconomic family is very detrimental to the community because in its activities, the loan sharks that develop among the people of Tanjung Unggat Kelurahan have tried to bring in excessive debt accumulation, so the interest to be given must also be more.